Capital accumulation in eastern and southern Africa : a decade of setbacks - Gulhati, Ravi.; Datta, Gautam (Washington, D.C. : World Bank, 1983)
The paper attempts to analyze the magnitude of the setback in capital accumulation in Eastern and Southern Africa and the proximate cause of this phenomenon. The sample consists of 16 countries and available data for the late 1960s and 1970s are explored.
Bibliography: p. 74.
usc 01/12/2021
Loans
Keywords: Saving and investment; Saving and investment; Capital productivity; Capital productivity